Radiogenomics Map Reveals the Landscape of m6A Methylation Modification Pattern in Bladder Cancer - Ye, Fangdie; Hu, Yun; Gao, Jiahao; Liang, Yingchun; Liu, Yufei; Ou, Yuxi; Cheng, Zhang; Jiang, Haowen (Frontiers in Immunology, 2021)
Purpose: we aimed to developed a noninvasive radiomics approach to reveal the m6a methylation status and predict survival outcomes and therapeutic responses of patients. Method: we constructed the methylation modification pattern based on the genomic data of 716 samples by performing unsupervised consensus clustering analysis. Then we classified patients into distinct clusters to quantify the m6A modification pattern of an individual sample based on the m6ascore by executing principal component analysis and evaluate the therapeutic response. In addition, a total of 98 obtained digital images were processed to capture the image signature and be constructed image prediction models based on the above classification by performing the radiomics algorism. Results: A total of 25 m6a regulators were collected for further analysis, we confirmed that expressional alteration and genomic mutation in m6a regulators between cancer and normal tissues were significantly difference. The m6a subtypes identified by the above method can effectively predict the clinical outcome of bladder cancer (including m6aClusters, geneClusters and m6ascore models). In addition, we also observed the immune response markers such as PD1, CTLA4 were significantly related to the m6ascore, patients with high m6ascore presented lower expression level of PD1 and CTLA4. Then using the TCIA database, we constructed a seven signature’ radiogenomics models to reveal the m6a methylation status and the model achieved an AUC degree of 0.887 and 0.762 on the training and test datasets. Conclusion: the presented radiogenomics models, a noninvasive prediction approach that combined the radiomics signatures and genomics characteristics, displayed satisfactory effective performance for predicting survival outcomes and therapeutic responses of patients. More interdisciplinary fields concerning the combination of medicine and electronic needed to be explored.